Tandem Fluorescent Protein Timers for Noninvasive Relative Protein Lifetime Measurement in Plants. Issue 2 (14th March 2019) - Zhang, Hongtao; Linster, Eric; Gannon, Lucy; Leemhuis, Wiebke; Rundle, Chelsea A.; Theodoulou, Frederica L.; Wirtz, Markus
Abstract : Tandem fluorescent protein timers enable non-invasive analysis of protein turnover in intact plant cells, allowing tests of how different genetic backgrounds and treatments affect protein stability. Abstract: Targeted protein degradation is an important and pervasive regulatory mechanism in plants, required for perception and response to the environment as well as developmental signaling. Despite the significance of this process, relatively few studies have assessed plant protein turnover in a quantitative fashion. Tandem fluorescent protein timers (tFTs) offer a powerful approach for the assessment of in vivo protein turnover in distinct subcellular compartments of single or multiple cells. A tFT is a fusion of two different fluorescent proteins with distinct fluorophore maturation kinetics, which enable protein age to be estimated from the ratio of fluorescence intensities of the two fluorescent proteins. Here, we used short-lived auxin signaling proteins and model N-end rule (N-recognin) pathway reporters to demonstrate the utility of tFTs for studying protein turnover in living plant cells of Arabidopsis ( Arabidopsis thaliana ) and Nicotiana benthamiana . We present transient expression of tFTs as an efficient screen for relative protein lifetime, useful for testing the effects of mutations and different genetic backgrounds on protein stability. This work demonstrates the potential for using stably expressed tFTs to study native protein dynamics with high temporal resolution in response to exogenous or endogenous stimuli.